Fuel cell flow path design for improved efficiency and power density - Ray, Madhusmita; Patel, Chirag G.; Jeong, Seongpil; Swaminathan, Jaichander (Elsevier BV, 2025)
Thermodynamic equipartitioning can improve the energy efficiency of a fuel cell at fixed size and fuel utilization by varying local cell potential to optimally distribute current density and electrochemical reaction rates over the electrode area. In practical systems however, potential across the end electrodes is fixed, resulting in higher current density near the inlet where reactant concentrations are highest. Here, a flow recirculation design for fuel and oxidizer streams is proposed to enable nearly uniform local current density distribution. The proposed configuration can achieve around 90 % of the thermodynamically feasible power enhancement, with higher improvement (up to 12 %) at a larger baseline system size. At a fixed power output, the design can also reduce area by 8 %-88 % through higher average current density operation. When cost-optimal system size is considered for both operating modes, a 2-6 % reduction in specific cost of energy can be achieved, with greater savings at higher fuel price compared to amortized cost of system area. Axial electrical conduction in the bipolar plates reduces energy efficiency improvements. Therefore, methods to limit axial conduction, such as reducing plate thickness or increasing its resistivity in the flow direction, are necessary to realize the full potential of the proposed design.